2012
DOI: 10.4149/neo_2012_017
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Radiochemotherapy With Weekly Cisplatin in Patients With Head and Neck Cancer Single-Institution Outcome Analysis

Abstract: The objective of this study was to evaluate the feasibility, toxicity and efficacy of postoperative radiochemotherapy with weekly cisplatin in locoregionally advanced or high risk head and neck cancer in a single institutional setting.Patients with head and neck cancer of stage III/IV or patients with insufficient margins of resection were included in the study. Radiotherapy consisted of 70 Gy/ 7 weeks/ 35 fraction after R1/2 resection and 60-64 Gy/ 6-6,5 weeks/ 30-32 fraction after R0 resection, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
2
7
0
1
Order By: Relevance
“…In a study using the same accelerated RT schedule, we observed a similar incidence of confluent mucositis of 79%, which indicates that concomitant weekly cisplatin does not further enhance mucosal toxicity . Studies using conventional RT combined with weekly cisplatin showed 31% to 75% mucositis ≥ grade 3, but similar rates of hematological and renal toxicity as we found . Hospital admissions were required in 55% of our patients, 40% for acute reasons and 15% for logistical reasons.…”
Section: Discussionsupporting
confidence: 78%
“…In a study using the same accelerated RT schedule, we observed a similar incidence of confluent mucositis of 79%, which indicates that concomitant weekly cisplatin does not further enhance mucosal toxicity . Studies using conventional RT combined with weekly cisplatin showed 31% to 75% mucositis ≥ grade 3, but similar rates of hematological and renal toxicity as we found . Hospital admissions were required in 55% of our patients, 40% for acute reasons and 15% for logistical reasons.…”
Section: Discussionsupporting
confidence: 78%
“…Contrary to expectations, the incidence of treatment interruptions was significantly higher (41% vs 22%; p=0.005) in the weekly cisplatin arm (Geeta et al, 2006). Frequent omission of weekly cisplatin (40 mg/m 2 ) due to haematological toxicity has also been reported by Pala et al (2012). Similar to this, Mitra et al found more number of treatment interruptions in weekly CT group, which might be explained by higher percentage of patients with significant weight loss in the weekly group.…”
Section: Treatment Interruptionsupporting
confidence: 66%
“…Nine single-arm studies evaluated the efficacy of adjuvant CRT. [23][24][25][26][27][28][29][30][31] Of these, six were prospective trials. 23,24,26,28,30,31 Data gathered in these studies covered a period from 1980 to 2009.…”
Section: Literature Search Resultsmentioning
confidence: 99%